Prophet Muhammad (Peace Be Upon Him) From Birth To Prophet Hood - Khan, Musaddiq Majid (University of the punjab, Lahore, Pakistan, 2017)
This study proposes to analyze and exploration of the basic structure of the agreed upon events of the Al-Sīrahof Prophet Muhammad (Peace be Upon Him). In addition to that this study intends to overcome the logic of defense -As much as possible- to make the abstract facts themselves constitute, in the mind of the reader, the true presentation of Al-Sīrah, and refute all what is commented in the past and present such as diluted and fabricated narrations, which did not have to withstand in front of the historical incident itself, because the historical events are considered as judgments and best judges itself sometimes. Thus there is a need to refer to the basic sources in the subject (especially Al-Sīrah of IbnHisham, ṬabaqātIbnSaʿd, Tārīkh Al-Ṭbrī, Maghāzī, Al-Wāqidī , Ansāb Al-Blādhrī and al-Ṣaḥīḥ Al-Bukhārī...), and to deal directly with them, to avoid the overflow of the late sources and the improvisation of modern references. These are two necessary issues to build a picture close to historical reality as much as possible. Based on this methodology our focus in this paper will be on the period from the birth of Prophet Muhammad (Peace be Upon Him) till His prophesy.